Cross-stream education pathways: academic performance and transition experiences of arts students in a science diploma program - Mohamadin, Mohammad Isa; Julaihi, Nor Hazizah; Abdul Karim, Siti Kartina (Penerbit UiTM (UiTM Press), 2026)
Malaysia’s long-standing Science-Arts streaming policy has contributed to a decline in STEM participation. Implemented in 1967, it has yet to achieve its intended goals. This shortfall has prompted initiatives such as cross-stream admissions to widen access to science education. At Universiti Teknologi MARA (UiTM), Arts-stream students are admitted into the Diploma in Science (AS120). However, there is limited evidence available on their performance and experiences. This study examined the academic outcomes, motivations, challenges, and aspirations of Arts-stream students in AS120 using students’ academic performance records (CGPA and PLO attainment) and survey responses. Findings indicated that Arts-stream students achieved moderate CGPA and generally met PLO benchmarks, particularly in applied and skill-based domains. However, gaps in the PLO1 and PLO2 (knowledge and cognitive competencies) require additional instructional support. Survey analysis revealed that students were primarily motivated by career prospects and personal interest, while mathematical difficulties emerged as their greatest academic barrier. Descriptive patterns further showed that students motivated by career prospects and personal interest were more likely to report academic challenges (more than 63%). These included mathematical difficulty, gaps in foundational knowledge and the fast pace of learning. Others reported psychosocial challenges such as low confidence, poor time management, stress, and a lack of belonging. Regarding aspirations, most students (58.6%) planned to pursue science-related bachelor’s degrees. A smaller group (24.1%) intended to switch to non-science fields, while others remained uncertain. Although 76% of students agreed that the cross-stream policy supported their plans, only 55% would stick to AS120 given a second chance. This shows some ambivalence. Overall, the findings suggest that the policy has broadened access and fostered pathways into science. However, sustained engagement in STEM requires stronger academic bridging in mathematics and science fundamentals. It is also a call for psychosocial interventions such as mentoring and confidence-building. Future research should adopt longitudinal, multi institutional designs to assess long-term outcomes and identify best practices for cross-stream integration.